(untitled) (Conferencea, 2022)
The article tells about disabled children born as a result of marriage between relatives. Information is provided on some of the most common hereditary diseases resulting from mating colors between same-sex couples. This article emphasizes that if parents want their children to be happy, then achieving a healthy generation is the most important goal.